Designing an E-Learning Application with Diagnostic Learning Style Testing for Enhancing Personalization in Educational Technology Courses - Kurniadi, Denny; Wagino, Wagino; Asnur, Lise; Safitri, Rahmadona; Koto, Rahmat Desman; Wakhinuddin, Wakhinuddin (Universitas Negeri Padang, 2025)
Teaching the importance of personalized learning in educational technology courses encourages students to understand how tailored educational approaches can enhance learning outcomes. Diagnostic learning style testing, including visual, auditory, kinesthetic (VAK), and technology usage dimensions, has been widely recognized as an effective method for addressing diverse student needs. The purpose of this paper is to design an e-learning application with diagnostic learning style testing to enhance personalization in educational technology courses. This system evaluates learning styles based on five dimensions and uses diagnostic results to recommend personalized learning strategies. The application is implemented as a web-based platform, providing both theoretical insights and practical application. By utilizing this system, educators and learners can gain actionable insights into individual learning preferences, ensuring better alignment between teaching methods and student needs. Additionally, the e-learning application can be accessed via mobile devices, allowing for flexible and adaptive learning experiences anytime and anywhere.